Procedures and Lexicons Used in Ngerorod Wedding Ceremony in Sidetapa Village North Bali - Dewa Ayu Oka, Angelita (Journal of Linguistic and Literature Studies, 2024)
This research aimed to describe the procedures, lexicons, and cultural meanings found in the ngerorod wedding ceremony in Sidetapa village. This research was designed in the form of descriptive qualitative research. The data of this study were collected through observation, interview, recording, and documenting. Three informants in this study were selected based on a series of criteria. The instruments used in this research were a camera, interview guide, and observation sheet. This study's results showed seven procedures in the ngerorod wedding ceremony in Sidetapa village and twenty-seven lexicons in the ngerorod wedding ceremony in Sidetapa village. The seven procedures found in the ngerorod wedding ceremony in Sidetapa village are ngelaibang, ngaku nyuwang/mepejati, ngengkeb, ngabe iyeh, mesuwaka, makruna, and pejalan bebas/bebas pejalan. In addition, twenty-seven lexicons found in ngerorod wedding ceremony are ngelaibang, ngaku nyuwang/mepejati, kanti, ngengkeb, ngabe iyeh, pengenduh, mesuwaka, makruna/pakrunan, damar, base tampil, penyapadana, purusa, pradana, saang, gagapan, pretaksu, umah adat, pejalan bebas/bebas pejalan, duwase, base palpalan, tetempeh, saling sopin, kain pejekjek, sesangi, natab banten bale, bobok, and ngabe saang.